Methods of Comparison of the Economic Order Quantity and Just-In-Time Restocking Technologies. The Case Study - Andrii Galkin; Velerii Levada; Volodymyr Kyselov; Oksana Hulchak; Dmytro Prunenko; Iryna Voronko (Communications - Scientific letters of the University of Zilina, 2022)
Estimation of the optimal size of order is one of the key tasks in determining the parameters of the urban freight restocking system. The existing analytical models and methods are considering each technology separately and they do not compare the Economic Order Quantity (EOQ) and Justin-tme (JIT) restocking technologies. The purpose of this research was to evaluate efficiency of the JIT and EOQ restocking technologies. The research would help in selecting the delivery model, analyzing functioning of existing JIT and EOQ models. The article presents an approach to determining the comparison in organizing supplies to the retailer. For this, the two supply models were compared. The Just-in-Time model is characterised by costs that are spend on transportation. The Economic Order Quantity model includes costs of transportation and storage in a warehouse. After calculations, application of the Just-in-Time model in the given conditions was determined.